Dioscorea alata L. Tubers Improve Diabetes through Anti-hyperglycemia, Anti-inflammation, Ameliorate Insulin Resistance and Mitochondrial Dysfunction - Sri Nabawiyati Nurul Makiyah; Masaki Kita; Ika Setyawati; Sri Tasminatun (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Dioscorea alata L. tubers (DA) are suspected to prevent diabetes mellitus (DM) because they have a low glycemic index. However, only a few reports about the anti-diabetic effect of DA were reported up to date. This study aims to analyze the effect of DA consumption on several diabetic biomarkers through in vitro, in vivo, and in silico analysis.METHODS: In vitro experiments were conducted by observing the anti-inflammatory activity of DA extract, steroidal saponins (SDA) isolated from DA, and diosgenin in lymphocyte cell cultures. The tumor necrosis factor (TNF)-α and interferon (IFN)-γ percentages were analyzed by flow cytometry. In vivo study involved 24 healthy adolescents that were given a boiled DA 10 hours post-prandial. The blood sugar levels were measured at 0, 30, 60, and 120 min after treatment. Furthermore, the in silico study was carried out by analyzing the active compounds and predicting the biological activity, the target proteins, and interactions of target proteins with compounds contained in DA .RESULTS: DA extract, SDA isolated from DA, and diosgenin at 50 µg/mL significantly reduced pro-inflammatory cytokines TNF-α and IFN-γ in lymphocyte cell culture. The blood glucose levels in the DA group were lower at 30 and 60 min after treatment. Based on the in silico study, the anti-diabetic activity of DA was speculated to be attributed to the mechanisms of anti-hyperglycemia, prevention of mitochondrial dysfunction, anti-inflammation, and treated insulin resistance. Several proteins included in the DM pathway became the protein target of compounds contained in DA.CONCLUSION: DA potentially have an anti-diabetic activity through several mechanisms.KEYWORDS: hyperglycemia, inflammation, insulin resistance, yam